VD_FINDINFO AP / 2009 / 153 vom 27. Mai 2009 - VD Tribunal cantonal (2009)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, RÉCIDIVEINFRACTION, ANTÉCÉDENT, FIXATION DE LA PEINE | 42 ch. 1 CP, 42 CP, 43 ch. 1 CP